Meridional changes in the South Atlantic Subtropical Gyre during Heinrich Stadials - Pinho, Tainã M. L. (Sci Rep, 2021)
Subtropical ocean gyres play a key role in modulating the global climate system redistributing energy between low and high latitudes. A poleward displacement of the subtropical gyres has been observed over the last decades, but the lack of long-term monitoring data hinders an in-depth understanding of their dynamics. Paleoceanographic records offer the opportunity to identify meridional changes in the subtropical gyres and investigate their consequences to the climate system. Here we use the abundance of planktonic foraminiferal species Globorotalia truncatulinodes from a sediment core collected at the northernmost boundary of the South Atlantic Subtropical Gyre (SASG) together with a previously published record of the same species from the southernmost boundary of the SASG to reconstruct meridional fluctuations of the SASG over last ca. 70 kyr. Our findings indicate southward displacements of the SASG during Heinrich Stadials (HS) 6-4 and HS1, and a contraction of the SASG during HS3 and HS2. During HS6-4 and HS1, the SASG southward displacements likely boosted the transfer of heat to the Southern Ocean, ultimately strengthening deep-water upwelling and CO(2) release to the atmosphere. We hypothesize that the ongoing SASG poleward displacement may further increase oceanic CO(2) release.